(3EYGOI GdJCejf Hjf GdfXQjI hGdJWHjb (B=s Reinsurance between theory and application - (3TcQj, HgGA HgjLs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3jJMOK GdcJGH Yf EYGOI GdJCejf Hjf GdfXQjI hGdJWHjb MjK jeQ fXGe GdJCejf aj GdJWHjb GdYedj HKdGK eQGMd gj eQMdI GdJCejf GdeHGTQ, hJJeKd HGdJYGbO Hjf GdeDef dge hGdeDef GdeHGTQ Ydi JZWjI GdCNWGQ GdJj jTJQchf aj GdNTjI ef fJGFLgG heQMdI EYGOI GdJCejf hJJeKd HGdJYGbO Hjf GdeDef GdeHGTQ heYjO GdJCejf dJZWjI eSDhdjI GdChd Yf JYhjV GdNSGFQ GdJj JdMb HGdeDef dge CeG GdeQMdI GdKGdKI aJJeKd HeG jYQa HGdESfGO GdecQQ hHehLHgG jZWj eYjO GdJCejf eSDhdjJg Yf fJGFL GdCNWGQ GdeSfOI dg ef bHd GdeDef GdeHGTQ(B. s
(3JUeje hEfJGL (B: (3ecJH OGQ GdKbGaI ddJUeje hGdEfJGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B303.s
Keywords: (3EYGOI GdJCejfs; (3GdJYhjVGJs; (3GdeGdjIs